2020
DOI: 10.26464/epp2020024
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-6-day waves in the mesosphere and lower thermosphere region and their possible coupling with the QBO and solar 27-day rotation

Abstract: Key Points:Features of seasonal variations in the 6DWs are significant, and these seasonal features are slightly different in the mid-low latitudes qThe annual oscillations of the 6DWs in the mid-low latitudes are modulated by the quasi-biennial oscillation in the diurnal tide, resulting in seasonal features that are different from those at other latitudes q The 6DW amplitudes at mid-high latitudes has a significant 27-day solar rotation variation. q Citation: Wang, J. Y., Yi, W., Chen, T. D., and Xue, X. H. (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The 10 days (8-12 days) and 16 days (12-20 days) waves in the high latitudes obtained from the DMR, SMR, and TMR, in higher middle latitudes obtained from the MMR are mainly enhanced during winter and are weak during summer. The statistics of planetary waves (2-16 days) using the meteor radars in this study are generally consistent with the results described by Murphy et al (2007) using Davis MF radar wind and hydroxyl rotational temperature measurements, and those of Gong et al (2018Gong et al ( , 2020 and Wang et al (2020) using the MMR and BMR meteor radar wind measurements. Generally, the amplitudes of planetary waves are strongest in the SMR temperatures; and the amplitudes of planetary waves in northern high latitudes are greater than that of in southern latitudes.…”
Section: Seasonal Variations Of Mesopause Temperature and Hemisphericsupporting
confidence: 88%
See 1 more Smart Citation
“…The 10 days (8-12 days) and 16 days (12-20 days) waves in the high latitudes obtained from the DMR, SMR, and TMR, in higher middle latitudes obtained from the MMR are mainly enhanced during winter and are weak during summer. The statistics of planetary waves (2-16 days) using the meteor radars in this study are generally consistent with the results described by Murphy et al (2007) using Davis MF radar wind and hydroxyl rotational temperature measurements, and those of Gong et al (2018Gong et al ( , 2020 and Wang et al (2020) using the MMR and BMR meteor radar wind measurements. Generally, the amplitudes of planetary waves are strongest in the SMR temperatures; and the amplitudes of planetary waves in northern high latitudes are greater than that of in southern latitudes.…”
Section: Seasonal Variations Of Mesopause Temperature and Hemisphericsupporting
confidence: 88%
“…(2018, 2020) and Wang et al. (2020) using the MMR and BMR meteor radar wind measurements. Generally, the amplitudes of planetary waves are strongest in the SMR temperatures; and the amplitudes of planetary waves in northern high latitudes are greater than that of in southern latitudes.…”
Section: Seasonal Variations Of Mesopause Temperature and Hemisphericmentioning
confidence: 99%
“…In the past decades, there have been many reports of planetary waves in the MLT region. Planetary waves are usually observed for periods of around 2, 4–7, 8–12, and 12–20 days (e.g., Manson and Meek, 1986; Mitchell et al, 1999; Miyoshi, 1999; Riggin et al, 2006; Pancheva et al, 2008; Gan Q et al, 2015; John and Kumar, 2016; Huang CM et al, 2017; Huang YY et al, 2017; Ma Z et al, 2017; Gong Y et al, 2018, 2019; Wang JY et al, 2020). Researchers (e.g., Charney and Drazin, 1961; Salby, 1981a, b; Forbes et al, 1995) have suggested that planetary waves in the MLT region are generated in situ or that they are excited in the troposphere and stratosphere and then propagate into the MLT.…”
Section: Introductionmentioning
confidence: 99%